Non-pharmaceutical Chinese medical therapies for degenerative lumbar spinal stenosis: A systematic review and meta-analysis of randomized controlled trials - Ya-nan Sun; Yi An; Yan-Ji Zhou; Xi-You Wang; Chang-He Yu (Complementary Therapies in Medicine, 2023)
Objective: The objective of the study was to assess the effectiveness of utilizing Non-Pharmaceutical Chinese Medical (NPCM) therapy singularly or in combination for the treatment of Degenerative Lumbar Spinal Stenosis (DLSS). Methods: The comprehensive search for all randomized controlled trials regarding NPCM therapies for the treatment of DLSS was performed through online databases searches, commencing from their inception to January 1st, 2023. The relevant literature underwent a thorough screening process, and the data was meticulously extracted and subjected to analysis through the implementation of RevMan 5.3 software. The Cochrane Risk of Bias tool was employed to assess the potential risk of bias. The synthesis of evidence was performed Grading of Recommendations Assessment, Development, and Evaluation. Results: The extensive search procedure produced 5674 records, including data from 37 studies of 38 comparisons (2965 participants). Moderate evidence was obtained demonstrating that the application of acupuncture for a duration of 6–8 weeks was significantly superior to sham acupuncture in terms of intermediate-term (6 months) alleviation of back pain (2 trials, n = 128; MD, −1.08; 95% CI, −1.81∼−0.34) and improvement in lumbar function (2 trials, n = 128; MD, −1.40; 95% CI, −2.93∼−0.13). The available low evidence suggested that, as compared to sham acupuncture, acupuncture was effective in reducing short-term (3 months) back pain and enhancing lumbar function but had no impact on leg pain. A trial with low risk of bias found that acupuncture was more effective than sham acupuncture in enhancing disability and walking capabilities. The other studies presented inconsistent evidence with regards to the efficacy of the various interventions employed. Conclusions: Evidence of low-to-moderate quality suggests that for DLSS patients, the implementation of acupuncture in comparison to sham acupuncture presents favorable outcomes in terms of short- and intermediate-term alleviation of back pain, improvement in lumbar function, enhancement of disability and walking capacity. The conclusion regarding the efficacy of other NPCM therapies was not obtained due to the insufficient quality of the available evidence.Registration: PROSPEROCRD42022307631.